Innovation cycles as a strategic methodological objectivity of the new technological paradigm of socio-economic development - Prokhorova, Viktoriia; Mushnykova, Svitlana; Abernikhina, Iryna; Yukhman, Yaryna; Makovoz, Olena; Slastianykova, Krystyna (Technology audit and production reserves, 2025)
The object of research is the processes of socio-economic development in the context of technological transformation, taking into account innovation cycles. The paper examines the role of innovation cycles as a strategic methodological objectivity that determines the dynamics of socio-economic development in the context of the transition to a new technological paradigm. The relevance of the topic is due to the global challenges of our time: digitalization, digitalization of the economy, development of artificial intelligence, transition to a green economy and the need to formulate adaptive development strategies that can respond to the pace of technological change. Innovation cycles are viewed as a multi-stage process that includes emergent ideas, new technologies, mass adoption of innovations and their impact on the structure of production, employment and institutional models. On the basis of historical and theoretical analysis, the paper traces the evolution of industrial revolutions – from Industry 1.0 to the anticipated Industry 6.0. It is noted that each new phase of industrial development is accompanied by the formation of a new technological paradigm that changes the principles of interaction between technology, capital, labor and knowledge. Industry 6.0, as the expected next stage, is associated with the symbiosis of artificial and biological intelligence, autonomous economies, decentralized management structures and value-oriented innovation development. The author substantiates the need to understand innovation cycles not only as an empirical phenomenon, but also as a methodological basis for strategic planning. In this context, the paper proposes a conceptual model that provides for the integration of cyclical analysis into the processes of state regulation, forecasting and formation of sustainable growth policies. The conclusions presented are of interdisciplinary importance and can serve as a basis for further research in the fields of economics, sociology, public administration and technological development.